2015
DOI: 10.1051/0004-6361/201424915
|View full text |Cite
|
Sign up to set email alerts
|

Can we constrain the interior structure of rocky exoplanets from mass and radius measurements?

Abstract: Aims. We present an inversion method based on Bayesian analysis to constrain the interior structure of terrestrial exoplanets, in the form of chemical composition of the mantle and core size. Specifically, we identify what parts of the interior structure of terrestrial exoplanets can be determined from observations of mass, radius, and stellar elemental abundances. Methods. We perform a full probabilistic inverse analysis to formally account for observational and model uncertainties and obtain confidence regio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
367
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(372 citation statements)
references
References 64 publications
5
367
0
Order By: Relevance
“…In the solar system the Sun's photospheric relative Fe-abundance can Article published by EDP Sciences L13, page 1 of 5 thus be used as a proxy for the iron mass fraction for three out of four terrestrial planets. This fraction is in turn a key quantity for the characterization of exoplanets: from measurement of mass and radius alone, the interior composition can only be weakly constrained owing to model degeneracies (Dorn et al 2015). It is thus interesting to see whether for the planets analyzed by Dressing et al (2015), a compositional correlation between the host stars and their planets is possible, suggesting that it may not be restricted to the solar system case.…”
Section: Introductionmentioning
confidence: 99%
“…In the solar system the Sun's photospheric relative Fe-abundance can Article published by EDP Sciences L13, page 1 of 5 thus be used as a proxy for the iron mass fraction for three out of four terrestrial planets. This fraction is in turn a key quantity for the characterization of exoplanets: from measurement of mass and radius alone, the interior composition can only be weakly constrained owing to model degeneracies (Dorn et al 2015). It is thus interesting to see whether for the planets analyzed by Dressing et al (2015), a compositional correlation between the host stars and their planets is possible, suggesting that it may not be restricted to the solar system case.…”
Section: Introductionmentioning
confidence: 99%
“…The achieved high precision in chemical abundances allowed observers to study the chemical abundances of stars with and without planets in detail (e.g., Gilli et al 2006;Robinson et al 2006;Delgado Mena et al 2014Kang et al 2011;Adibekyan et al 2012aAdibekyan et al ,b, 2015c. These studies are very important since the chemical abundances of stars with planets provide a huge wealth of information about the planet formation process (e.g., Bond et al 2010;Delgado Mena et al 2010), composition of planets (e.g., Thiabaud et al 2014;Dorn et al 2015;Santos et al 2015), and Based on data obtained from the ESO Science Archive Facility under request number vadibekyan204818, vadibekyan204820, and vadibekyan185979.…”
Section: Introductionmentioning
confidence: 99%
“…Grasset et al 2009;Bond et al 2010;Delgado Mena et al 2010;Rogers & Seager 2010;Thiabaud et al 2014Thiabaud et al , 2015Dorn et al 2015). Among the most important mineralogical ratios are the Mg/Si, Fe/Si, and C/O ratios that can be used to constrain the chemical composition of terrestrial planets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important mineralogical ratios are the Mg/Si, Fe/Si, and C/O ratios that can be used to constrain the chemical composition of terrestrial planets (e.g. Bond et al 2010;Thiabaud et al 2015;Dorn et al 2015). Recently, Dressing et al (2015) showed that all the terrestrial planets in their sample with masses lower than 6 M ⊕ lie in the same mass-radius area as Earth and Venus.…”
Section: Introductionmentioning
confidence: 99%